RITUAL SESAPA PADA UPACARA PAWIWAHAN DI LOMBOK - Ni Komang Wiasti (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
Hindus have a variety of characteristics of the five ceremonies as the basic hierarchical foundation in carrying out their beliefs as religious people. Each yadnya will be clearly observ- able in the ritual process of the ceremony to make it appear more attractive, the atmosphere becomes more sacred and religious. In Lombok at the pawiwahan ceremony there is a meaning- ful ritual process, delivered in a humorous manner, using very simple language, aiming to pray for the bride and groom to live a prosperous and happy life. Currently, there is a paradigm shift in thinking about the greeting because the public's perception of it is considered pornographic, excessive, so that it will disturb the situation of the sanctity of the temple of merajan, or its denial. The formulation of the problem consists of: What is the form of sesapa at the pawiwahan ceremony in Lombok; process of the sesapa ritual at the pawiwahan ceremony in Lombok. In general, the purpose of this study is to describe and analyze the sesapa ritual at the pawiwahan ceremony in Lombok and to contribute to the preservation of the noble Hindu culture. This research is descriptive qualitative where the results of the research will be described the form sentences. With a theoretical basis referring to Interpersonal theory, Action Theory, and Sym- bolic Interactional Theory to dissect the formulation of the problem studied. The forms of the sesapa ritual at the pawiwahan ceremony in Lombok include: Mepejati, Meketelun, Ngendek, Inflammation, adult ngerereh. while the sesapa ritual process at the pawiwahan ceremony in Lombok begins with Mewidhi Widhana by starting with Mebyakala, Natab Banten and Mejaya- jaya, Nyongkolan and Mekunyit Keladi, Mejanguk and the meanings contained in the sesapa ritual at the pawiwahan ceremony in Lombok, namely: as the meaning of purification, means of meaning supplication and meaning of Welfare.Keywords: Sesapa Ritual, Pawiwahan